The Influence Of Intellectual Capital And Good Corporate Governance On The Value Of Infrastructure Sector Companies Listed On The Indonesia Stock Exchange - Adi, Firdaus Maulana; Kurniasih, Augustina (Publikasi Indonesia, 2024)
This research is a quantitative analysis that aims to evaluate the impact of intellectual capital and good corporate governance on company value. The study was conducted on companies engaged in infrastructure listed on the Indonesia Stock Exchange during the 2017-2021 period. Corporate Value is identified through Price to Book Value (PBV), while Intellectual Capital is identified using Value Added Capital Employee (VACA), Value Added Human Capital (VAHU), Structure Capital Value Added (STVA), while Good Corporate Governance identified using Independent Commissioners, Audit Committee and Internal Auditor as well as Managerial Ownership. The research sample amounted to 30 issuers obtained through the purposive sampling method. The results of the study explained that VACA has a significant negative effect on the Company's value, VAHU has a significant positive effect on the Company's value, STVA has a positive but not significant effect on the Company's corporate value, Independent Commissioners have a negative and insignificant effect on the Company's value, the Audit Committee and Internal Auditors and Managerial Ownership have a significant negative effect on the Company's value.